Faktor-Faktor Yang Mempengaruhi Cash Holding Pada Perusahaan Bumn Yang Terdaftar Di BEI - Nicholas Edward, Herlin Tundjung (Jurnal Paradigma Akuntansi, 2021)
The aim of this study was to find out  empirical evidence of accounting cash flow, leverage, good corporate governance toward cash holding at state-owned enterprises listed in Indonesia Stock Exchange in 2014-2018. This study used 17 national companies that have been selected using purposive sampling method with total 85 data for 5 years. This research data processing using Eviews version 9.0. The result of research shows that: 1) Cash Flow has no significant Cash Holding; 2) leverage a significant effect on Cash Holding; and 3) GCG has no significant effect on Cash Holding.